Life expectancy discussions in a multisite sample of Australian medical oncology outpatients. Issue 10 (16th November 2015) - Zucca, Alison C; Sanson‐Fisher, Rob W; Waller, Amy; Carey, Mariko; Grady, Alice; Mackenzie, Lisa
Abstract: Objectives: The study examined: 1) the proportion of patients who received their preferred level of information about life expectancy; and 2) sociodemographic, clinical and psychological factors associated with patients' perceptions of whether they received too little, too much, or the right amount of information about life expectancy. Design: Cross‐sectional survey. Setting: Eleven large Australian medical oncology treatment centres. Participants: A total of 1431 medical oncology outpatients participated (81% consent rate). Eligible patients were approached between September 2012 and May 2014. Main outcome measures: Patients indicated whether the information about life expectancy they received aligned with their preferences. Results: Almost one in four patients (24%) received too little information, 4% received too much, and 50% received all the information they wanted; 22% of patients neither wanted nor received information about life expectancy. Patients were more likely to receive too little information if they were not in remission (odds ratio [OR], 1.77), did not know their cancer stage at diagnosis (OR, 3.64), or were anxious (OR, 1.48) or depressed (OR, 1.48). Patients had greater odds of receiving too much information if they were younger (OR, 1.45), had more advanced cancer (OR, 2.01) or did not know their cancer stage at diagnosis (OR, 4.42). Conclusions: That fact that 28% of cancer patients did not receive their desired level of information about life expectancy highlights the difficulties associated with discussing this sensitive topic. To ensure that life expectancy discussions correspond with patient preferences, clinicians should routinely ask patients whether they want to know this information, in what format, and at which level of detail.